The role of foreign direct investment by multinational corporations in Africa - Asnake Anteneh Chanie (Journal of BRICS Studies)
Foreign direct investment in conflict-affected areas is a contentious issue in the study of economic development and international human rights. Some analysts are enthusiastic about foreign direct investment (FDI) in conflict-affected areas, claiming that it supports economic growth and play a constructive role in peace-building efforts. On the other hand, a substantial body of literature suggests that FDI in conflict-torn areas may exacerbate instability and negatively undermine economic growth.